Sequence variant at 8q24.21 associates with sciatica caused by lumbar disc herniation - Gyda Bjornsdottir (Nature Portfolio, 2017)
Lumbar disc herniation (LDH) can cause persistent sciatica, and in some cases surgery is required to relieve symptoms. Here, the authors carry out a genome-wide association study using microdiscectomy as an indicator of severe LDH, and find a locus on chromosome 8 associated with this condition.